Elmo's world. Babies, dogs & more! - Children's Television Workshop (New York : Children's Television Workshop : manufactured by Sony Wonder, 2000)
Everyone's favorite 3 year old is back in his special world! With his pet goldfish, Dorothy, and friend Mister Noodle, join Elmo as he explores the world of babies, dogs and life on the farm. Each self contained segment gives children a chance to experience their world on the TV screen and offers adults the opportunity to experience everyday things through a three-year-old's eyes. Featuring orginal and classic songs, each segment educates and delights viewers of all ages.
Babies -- Dogs -- Life on the farm.
At head of title: Sesame Street.
Executive producers, Arlene Sherman, Michael Loman ; directors, Ted May, Steve Feldman, Jim Martin, Ken Diego ; writers, Tony Geiss, Annie Evans, Emily Kingsley.
Starring Jim Henson's Sesame Street Muppet Performers: Kevin Clash as Elmo, Matt Vogel, John Tartaglia, Jim Martin, Caroll Spinney, Martin P. Robinson, Carmen Osbahr, John Mazzarino, Pam Arciero, Stephanie D'Abruzzo, and John Kennedy with a special appearance by Michael Jeter.
VHS.
Closed-captioned.
Keywords: Dogs -- Juvenile films; Farm life -- Juvenile films; Farms -- Juvenile films; Children's songs -- Juvenile films; Video recordings for the hearing impaired; Dogs; Farm life; Farms; Songs